Human perception of radon risk and radon mitigation: some remarks - Neznal, Martin; Neznal, Matěj (Radiation protection dosimetry, 2008)
The Radon program in the Czech Republic has a relatively long and rich history. Procedures, which enable to evaluate the risk of radon penetration from the ground, to protect new buildings, to find existing buildings with elevated indoor radon levels and to realise remedial measures in such buildings, have been developed, published and tested. In some cases, the whole system may fail due to psychological or sociological reasons. Three types of problems (conflicts) will be presented: human behaviour affecting measurement results, conflict between individual and 'all-society' points of view, interpretation of radon risk itself.
Keywords: Radiation Protection; postoj; Guideline Adherence; Radon; lidé; Air Pollution, Indoor; Radiation Dosage; Humans; radiační ochrana; Public Opinion; Attitude; směrnice jako téma; radon; Czech Republic; znečištění vzduchu ve vnitřním prostředí; Guidelines as Topic; veřejné mínění; dávka záření; Česká republika; dodržování směrnic